2′, 7′-dichlorofluorescin-based analysis of Fenton chemistry reveals auto-amplification of probe fluorescence and albumin as catalyst for the detection of hydrogen peroxide. Issue 24 (23rd December 2020) - Gonzalez, Teresa; Peiretti, Franck; Defoort, Catherine; Borel, Patrick; Govers, Roland
Abstract : Fluorophore 2′, 7′-dichlorofluorescin (DCF) is the most frequently used probe for measuring oxidative stress in cells, but many aspects of DCF remain to be revealed. Here, DCF was used to study the Fenton reaction in detail, which confirmed that in a cell-free system, the hydroxyl radical was easily measured by DCF, accompanied by the consumption of H2 O2 and the conversion of ferrous iron into ferric iron. DCF fluorescence was more specific for hydroxyl radicals than the measurement of thiobarbituric acid (TBA)-reactive 2-deoxy-D-ribose degradation products, which also detected H2 O2 . As expected, hydroxyl radical-induced DCF fluorescence was inhibited by iron chelation, anti-oxidants, and hydroxyl radical scavengers and enhanced by low concentrations of ascorbate. Remarkably, due to DCF fluorescence auto-amplification, Fenton reaction-induced DCF fluorescence steadily increased in time even when all ferrous iron was oxidized. Surprisingly, the addition of bovine serum albumin rendered DCF sensitive to H2 O2 as well. Within cells, DCF appeared not to react directly with H2 O2 but indirect via the formation of hydroxyl radicals, since H2 O2 -induced cellular DCF fluorescence was fully abolished by iron chelation and hydroxyl radical scavenging. Iron chelation in H2 O2 -stimulated cells in which DCF fluorescence was already increasing did not abrogate further increases in fluorescence, suggesting DCF fluorescence auto-amplification in cells. Collectively, these data demonstrate that DCF is a very useful probe to detect hydroxyl radicals and hydrogen peroxide and to study Fenton chemistry, both in test tubes as well as in intact cells, and that fluorescence auto-amplification is an intrinsic property of DCF.